(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this article, there is a wide range of processes for the production of modern materials for the recycling of waste derived from industrial waste, metallurgy, oral cavity, chemical technology, mining, q beating materials, wood and other industrial waste data is highlighted